Kinetics of Transesterification of Croton megalocarpus Oil Using Alkaline Earth Catalysts with Conventional and Microwave Heating - Anil Kumar; Henry K. Kiriamiti (International Journal of Chemical Engineering)
Transesterification kinetics of Croton megalocarpus oil to produce fatty acid methyl esters (FAME) was studied using homogeneous NaOH and heterogeneous alkaline earth Nano MgO, MgO, Nano CaO, CaO, Reoxidized CaO, SrO, and BaO catalysts. Characteristic surface, bulk, and chemical properties of the heterogeneous catalysts were obtained which included surface area, pore properties, scanning electron micrography, X-ray diffraction, basic strength, and basicity. The catalyst porosity varied as Nano MgO > Nano CaO > MgO > CaO > CaO-RO > SrO > BaO and basicity as BaO > SrO > Nano CaO > CaO RO > CaO > Nano MgO > MgO. Catalysts NaOH, BaO, SrO, and Nano CaO gave a good FAME yield (>50%), and reaction order and rate constant have been reported for these catalysts, for both conventional heating and microwave irradiation. The overall reaction for NaOH was of 1st order for microwave irradiation with respect to triglyceride and of 2nd order with respect to triglyceride under conventional heating. For the heterogeneous catalysts, the overall reaction was of 3rd order, 2nd order with respect to triglyceride and 1st order with respect to methanol for both heating methods. Reaction rate constants for microwave irradiation were higher than those for conventional heating due to faster reaction rates under such heating. BaO was the most active heterogeneous catalyst, followed by SrO and Nano CaO, which was in accordance with their basicity.